Analisis Kadar Kalsium (Ca) dan Fosforus (P) pada Limbah Sisik dan Sirip Ikan Mujair (Oreochromis mossambicus) dari Danau Lindu Sulawesi Tengah - Tiwow, Vanny M. A.; Hafid, Inda Widiarti; Supriadi, Supriadi (Jurnal Akademika Kimia, 2016)
The most fish species live in lake Lindu is mujair fish with the average number production of 1080 per day. The scales and fins of mujair fish are the biggest waste that is produced from the processing of this fish and they were just thrown away, which can pollute the environment. The aim of this study is to analyze the level of calcium (Ca) and phosphorus (P) on waste of mujair fish (scales and fins) from the lake Lindu as a basic ingredient of a liquid organic fertilizer. Samples of the scales and fins were taken from a seller mujair fish at Touwa street Palu. To analyze the level of calcium (Ca) and phosphorus (P) from the scales and fins was used a Spectrodirect. Based on the results of the analysis, the average of level of calcium (Ca) in the scales and fins was 4.98 mg/L and 33.33 mg/L, while the average of level of phosphorus (P) was 73.33 mg/L and 145.33 mg/L. The average concentration of dry weight of Ca in samples of the scales was 3,32 mg/kg and the fins was 22,22 mg/kg. The average concentration of the dry weight of P in samples of the scales was 48,88 mg/kg and the fins was 96,88 mg/kg. The results of this analysis showed that the highest concentration of calcium (Ca) and phosphorus (P) was in the fins of mujair fish.